Botulinum toxin-A in acute acquired comitant esotropia during COVID pandemic in children and young adolescents - Neelam Pawar; Praveena Shyam; Meenakshi Ravindran; Fathima Allapitchai (Indian Journal of Ophthalmology)
Purpose: To study the effectiveness of botulinum toxin A (BTX-A) in the treatment of patients with acute acquired comitant esotropia (AACE) due to excessive use of mobile and laptops in the COVID era in the pediatric population and adolescents. Methods: This was a retrospective, interventional study of pediatric patients and young adults who presented with AACE and received unilateral or bilateral BTX-A. All the patients complained of binocular diplopia and sudden onset of esotropia with a history of mobile or laptop usage during the COVID era (2020–2023). Twenty-seven patients with acute-onset esotropia in 3 years (2020–2023) were included. All patients were administered 2.5–7.5 units of BTX-A (Botox, Allergan, India) into the unilateral or bilateral medial rectus muscle of the deviating eye under short general anesthesia or local anesthesia. The main outcome measures were pre- and post-injection angle of deviation, pre- and post-injection stereopsis, final level of stereopsis achieved, recurrence, and whether strabismus surgery was later required. Results: The mean age of patients was 12.85 ± 7.15 years (range: 4–25 years). The mean dosage of Botox was 6 U (2.5–7.5 U). The mean follow-up was 6 months (6 months–2 years). The mean preoperative angle of deviation (AOD) was 41.11 ± 10.9 prism diopters (PD) for distance and 41.67 ± 10.9 PD for near. The maximum effect of BTX-A was seen at 1 month; post-injection AOD was 13.65 ± 14.7 PD for distance and 14.87 ± 15.8 PD for near (P < 0.001). Over half of the patients achieved optimal outcomes, with improvements in stereopsis and sensory fusion. Early intervention (within 3 months of symptom onset) significantly correlated with treatment success. Conclusion: While BTX-A therapy for acute-onset esotropia demonstrates efficacy, patient-specific considerations are essential. This study highlights the evolving nature in the digital age and early administration of BTX-A along with close follow-up to monitor residual and recurrence of esotropia. The surgical intervention can increase the final success rate.